Common mechanisms of autoimmune diseases (the autoimmune tautology) (2012)
The fact that autoimmune diseases share subphenotypes, physiopathological mechanisms and genetic factors has been called autoimmune tautology, and indicates that they have a common origin. The autoimmune phenotypes vary depending on the target cell and the affected organ, gender, ancestry, trigger factors and age at onset. Ten shared characteristics supporting this logical theory are herein reviewed. © 2012 Elsevier B.V.